Integrating positive psychology and spirituality in the context of climate change - Bellehumeur, Christian R.; Bilodeau, Cynthia; Kam, Christopher (Frontiers in Psychology, 2022)
With climate change and its accompanying impact on stress and mental health, we argue that positive psychology (PP) could benefit from integrating spirituality in order to better support people's well-being. Starting from an overview of climate change’s impact on well-being and health, we explore the paradoxical and complex relationship between humans and nature. Then, after briefly defining spirituality, we refer to an evocative metaphor of the wave as a way of portraying the evolution of the field of PP through the presentation of three waves of PP. In the discussion, we argue that the field of PP has gradually become more open to integrating spirituality (since the first wave), as it evolves towards greater complexity (in its third wave). Some spiritual perspectives potentially relevant to positive psychology facilitate an ecocentric view (i.e., eco-spiritualities) which allow for a better understanding of the paradoxical human-nature relationship, as we struggle to deal with the complex issues related to climate change.